Retrospective evaluation of R-EPOCH in the frontline treatment of adult patients with PTLD after solid organ transplant - Brian Cuzzo; Maegan Ford; Saagar Jain; Hua-Jay Cherng; Evelyn Orlando; Patrick Gould; Amy Song; Benjamin May; Yuxuan Chen; Govind Bhagat; Andrew H. Lipsky; Barbara Pro; et al. (Blood Neoplasia)
Abstract: Posttransplant lymphoproliferative disorders (PTLD) are rare complications of solid organ transplantation, which carry significant morbidity and mortality. Phase 2 trials that use sequential rituximab (R) followed by R, cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP) have become an acceptable approach for B-cell PTLD, although it carries a high risk of treatment-related mortality (up to 11%). Many aspects of B-cell PTLD biology and patient characteristics parallel AIDS-related lymphomas in which dose-modified R, etoposide, prednisone, vincristine, cyclophosphamide, and doxorubicin (DM-R-EPOCH) has been demonstrated to be highly efficacious and safe. In this single-institution retrospective study of (N = 101) adult transplant recipients with B-cell PTLD, 65 received DM-R-EPOCH, 8 received R-CHOP, and 17 received R monotherapy. Median progression-free and overall survival was 4.4 years and 6.4 years, respectively, for DM-R-EPOCH and 1 year and 1.1 years, respectively, for R-CHOP. Rates of neutropenia and infection were 70% and 77%, respectively, for DM-R-EPOCH, and 88% each for R-CHOP. Treatment-related mortality for patients treated with DM-R-EPOCH and R-CHOP was 4.7% and 25%, respectively. The median number of cycles of DM-R-EPOCH was 6, and between 73% and 89% of patients received a relative dose intensity of ≥80% for cyclophosphamide, etoposide, and doxorubicin. The relative dose intensity of vincristine was <80% in 56% of patients because of frequent omission for gastrointestinal involvement of PTLD. Collectively, these data suggest that DM-R-EPOCH does not lead to excessive toxicity in patients with B-cell PTLD and support the need for further prospective clinical studies.